SPIRITUAL TRAINING OF YOUNG ATHLETES - Dexqonov Bahodir Burxonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the results of the research carried out on the importance of training of young athletes in addition to the training of athletes are described.